Hyperglycemia Effects on Limbs Tingling and Twining Sensations - Khudhur, Samaa Faez (American Journal of Biology and Natural Sciences, 2025)
What Hyperglycemia Does to the Legs is quite devastated end with tragedy event of losing lower limbs, A patient with diabetic neuropathy (DN) may have both good and bad symptoms. On one hand, there are symptoms like pain, sensitivity, tingling, cramping, and cold feet. On the other hand, there are negative symptoms including sensory loss and delayed wound healing. The development and progression of DN cannot be explained solely by elevated blood glucose levels. New evidence suggests that a naturally occurring reactive metabolite called MG (methylglyoxal) can enhance function by modifying neuronal ion channels involved in chemo sensing and action potential generation in nociceptive nerve endings. This modification occurs after Glo1 ’’(glyoxalase I) levels are reduced. One possible reason for the development of DN is the effect of di carbonyls on the neuronal compartment. Thus, there may be new and improved ways to treat DN if we focus on preventing the buildup and effects of MG.’’